The requirements of a modern home - Spencer, Crete (My University, 1905)
Introduction: The subject of home building is important to every American. The modern home should have a distinct character particularly its own. It should have architectural beauty and attractiveness as well as all the modern requisites for utility. It is the work of the architect to consider carefully the needs of the housekeeper in order to make a convenient arrangement which will afford economy and ease, thus there is a distinct relation between the, work of the architect and that of the housekeeper. The housekeeping requirements depend upon the floor plan of the house and economy of work to the housekeeper depends upon its good construction. Interior construction and decoration are greatly related to the economy of work of the housekeeper. While it is well to consider the artistic qualities, these should not be elaborate. The term household conveniences is a somewhat modern one. "Those arrangements and appliances which make it possible for people to live more comfortable and in larger houses without seriously increasing the cares which they had in smaller ones" and making them more easily accomplished, "are called modern conveniences", or anything which saves labor may be regarded as a modern convenience. In the modern kitchen and laundry may be found the conveniences which are most appreciated by the housekeeper. Among some of these are: the arrangements for dish washing, the kitchen sink with faucets for hot and cold water, drain boards and drain pipes attached to sink. The modern laundry has the stationary wash tubs, water faucets and drain pipes with adjoining drying room which may be used during cold or stormy weather.
Home architecture
Citation: Spencer, Crete. The requirements of a modern home. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Household conveniences; hugienic conditions; bentilation; Theses